2021
DOI: 10.3390/nu14010016
|View full text |Cite
|
Sign up to set email alerts
|

The Timing and Duration of Folate Restriction Differentially Impacts Colon Carcinogenesis

Abstract: Diet plays a crucial role in the development of colorectal cancer (CRC). Of particular importance, folate, present in foods and supplements, is a crucial modulator of CRC risk. The role of folate, and, specifically, the synthetic variant, folic acid, in the primary prevention of CRC has not been fully elucidated. Animal studies varied considerably in the timing, duration, and supplementation of folates, leading to equivocal results. Our work attempts to isolate these variables to ascertain the role of folic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In a prostate cancer model, folate was found to be directly involved in oncogenic signaling pathways, specifically the PI3K-AKT-mTOR cascade [246]. Similarly, in a colon carcinogenesis mouse model, a significant increase in mTOR signaling was recorded in mice supplemented with folic acid compared with those without supplementation [20]. In addition to the observed effects on gene expression, FA was found to impact posttranslational modifications and protein-protein interaction [241].…”
Section: One-carbon-metabolism-independent Mechanismsmentioning
confidence: 98%
See 1 more Smart Citation
“…In a prostate cancer model, folate was found to be directly involved in oncogenic signaling pathways, specifically the PI3K-AKT-mTOR cascade [246]. Similarly, in a colon carcinogenesis mouse model, a significant increase in mTOR signaling was recorded in mice supplemented with folic acid compared with those without supplementation [20]. In addition to the observed effects on gene expression, FA was found to impact posttranslational modifications and protein-protein interaction [241].…”
Section: One-carbon-metabolism-independent Mechanismsmentioning
confidence: 98%
“…In rodent studies, excess folate can be defined as exceeding the accepted standard baseline supplementation of 2 mg/kg diet. However, the optimal folate requirements for animals may be lower, and the activity of rate-limiting one-carbon metabolism enzymes is typically much higher in rodents compared with humans [20][21][22][23]. Chow diets fed to laboratory rodents can contain a variable amount of FA ranging from 2 to 15 mg/kg diet and averaging about 8 mg/kg diet [22].…”
Section: Defining Excess Folatementioning
confidence: 99%
“…10 As an important probiotic in the human intestine, LABs can play an auxiliary or even major role in the prevention and treatment of diseases such as colitis, mucositis, and even the immunostimulation properties of colon cancer. 11 Their catabolism can produce a variety of vitamins for body growth, such as folic acid and riboflavin. 12 LeBlanc et al found that recombinant Lactococcus lactis with high folate-producing production can significantly improve folate levels in folate-deficient mice and partially restore macrocyte anemia caused by folate deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…As an important probiotic in the human intestine, LABs can play an auxiliary or even major role in the prevention and treatment of diseases such as colitis, mucositis, and even the immunostimulation properties of colon cancer 11 . Their catabolism can produce a variety of vitamins for body growth, such as folic acid and riboflavin 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Elevated FA levels are known for masking and exacerbating vitamin B12 deficiency [ 5 , 9 , 18 ], and are controversially implicated in increased cancer onset, progression, and mortality rate [ 5 , 18 , 19 , 20 ]. The controversies surrounding FA supplementation extend to a number of other diseases and conditions such as metabolic disorders [ 21 ], immunity [ 22 , 23 ], colon cancer [ 20 , 24 , 25 ], and autism spectrum disorders [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%